Application Analysis of Actual Scene Based on Analog Sending Device and Substation Client. Issue 2 (May 2021) - Che, Xiangbei; Liu, Qiangxing
Abstract: At present, all provinces have put into use the analog messenger device. The system has been put into use in large quantities and on a large scale, which has brought a series of operation and maintenance problems for field staff. Based on the collocation of the analog sender and the substation client, the application of the analog sender in the actual scene is analyzed. Research shows that under the condition of ensuring no communication interruption, this collocation method can enable maintenance personnel to realize physical isolation of maintenance equipment and operation equipment, which greatly improves the safety of maintenance work. In addition, the use of analog signaling devices can significantly reduce the impact on the operating part of the commissioning process, reducing the pressure on maintenance personnel.